The Mediating Role of Digital Citizenship in the Relationship between Digital Transformation Factors and E-Government Service Satisfaction - Phan Nhan Trung (PT. Riset Press International, 2026)
This study examines the mediating role of digital citizenship in the relationship between digital transformation factors and e-government service satisfaction among citizens in Ho Chi Minh City, Vietnam. Drawing upon the Technology Acceptance Model (TAM), the Expectation-Confirmation Theory (ECT), and Digital Citizenship Theory, a structural model was developed and tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 427 citizens who had utilized e-government services in Ho Chi Minh City through a structured questionnaire. The findings reveal that digital policy and institutional framework, and online public service design directly and significantly affect e-government service satisfaction. Furthermore, digital citizenship serves as a significant mediator in the relationships between all four digital transformation factors (technology infrastructure quality, digital capacity of public agencies, digital policy and institutional framework, and online public service design) and e-government service satisfaction. The results indicate that digital citizenship explains 58.3% of its variance, while e-government service satisfaction is explained by 61.2% of its variance. This study contributes to the theoretical understanding of how digital transformation influences citizen satisfaction through the mechanism of digital citizenship, and offers practical implications for policymakers seeking to enhance public service delivery in Vietnam.